Nosocomial infections and bacterial resistance in patients from a Teaching Hospital Intensive Care Unit - Adriana Cristina Oliveira; Bruno Horta; Glaucia Helena Martinho; Lorena Villa Dantas; Maíra Marques Ribeiro (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2007)
The Intensive Care Units represent an important and indispensable part of the modern medicine, for offering services to critically sick patients, using specialized human resources and advanced technology. In this study it was aimed to determine the incidence of the nosocomial infection, its possible relationship with the occurrence of the colonization by resistant microorganisms, the main agents of that colonization, and the mortality rate in that unit. It was a prospective and descriptive study, from August 2005 to July 2006. The data were collected from medical records and consultation to the microbiologic database. The global infection rate was 23,8%, the colonization for resistant microorganisms contributed to the development of infection (RR=6,8 [4,8-9,6], p <0,05), the resistant pathogens more prevalent were Pseudomonas aeruginosa and Acinetobacter baumannii. The mortality rate was 10,8%, and of these, 23 patients (37,1%) died after the diagnosis of nosocomial infection. Those results reinforce the need of efforts addressed to the control of the infection and of the bacterial resistance, subsidizing reflections in front of the adoption of measures such as the use of individual protection equipments, the invasive procedures, the handwashing, and the permanent education of the multiprofissional assistance team.